Strengthening Religious Moderation through Revitalizing Ma'had al-Jami'ah: A Case Study in the State Islamic Higher Education - Ahmadiono, Ahmadiono; Rahman, Fathor; Umam, Fawaizul (AL-TAHRIR, 2025)
This article aims to describe and discuss (1) the phenomenon of religious extremism on the campus and (2) institutional responses of the state Islamic higher education to it in the form of (3) strengthening religious moderation through the revitalization of Ma‘had al-Jami‘ah (Pesantren of University). With a case study research design and the religious moderation concept of the Ministry of Religious Affairs of the Republic of Indonesia as a theoretical framework, this study found relatively the same facts about the phenomenon of religious extremism in the three state Islamic universities. Their institutional responses also tend to be similar; they rely on the belief that religious extremism harms the spirit of Islam’s raḥmatan li al-'ālamīn and the movement of extreme religious elements has threatened the integrity of the Unitary State of the Republic of Indonesia. The biggest difference is the way the three campuses foster moderate religiosity of students through the revitalization of Ma‘had al-Jami‘ah. However, the various strengthening strategies they do are relatively in line with the strategy of strengthening religious moderation of the Ministry and therefore have productive values for the national program. These results contribute to enriching the discourse on religious extremism and can also be used as a reference for state Islamic universities in strengthening the early warning system, especially through the revitalization of Ma‘had al-Jami‘ah.